The effectiveness of the National Union Catalog and the Marcfiche as searching tools in the Cataloging Section of the Rizal Library - Lim, Corazon R. (1978)
This is an experimental study of Marcfiche, a catalog in microfiche containing the Library of Congress (LC) cataloging data and the L.C. National Union Catalog (NUC) a catalog in book form also containing LC cataloging data. This study tried to establish: 1) that the searching tool Marcfiche would minimize time spent in searching cataloging data for the new titles and 2) that Marcfiche as a searching tool would minimize the successful searches necessary for the early and speedy processing of the new acquisitions of the Rizal Library of the Ateneo de Manila University.